Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 174734 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Galium javalambrense López Udias, Mateo & M.B.Crespo", "TaxonKey is Orchis fragrans Ten.", "TaxonKey is Silene viridiflora Kotschy ex Rohrb.", "TaxonKey is Silene pseudoatocion Guss.", "TaxonKey is Stoibrax dichotomum (L.) Raf.", "TaxonKey is Teesdalia coronopifolia (Bergeret ex Steud.) Thell.", "TaxonKey is Narcissus ×perezlarae Font Quer", "TaxonKey is Teucrium edetanum M.B.Crespo, Mateo & T.Navarro", "TaxonKey is Quercus ×coutinhoi Samp.", "TaxonKey is Wahlenbergia nutabunda (Guss.) A.DC.", "TaxonKey is Zannichellia peltata Bertol.", "TaxonKey is Lappula marginata (M.Bieb.) Gürke", "TaxonKey is Glandora nitida (Ern) D.C.Thomas", "TaxonKey is Narcissus assoanus Dufour ex Schult. & Schult.f.", "TaxonKey is Cytisus malacitanus Boiss.", "TaxonKey is Silene tomentosa Otth", "TaxonKey is Leontodon microcephalus (Boiss. ex DC.) Boiss.", "TaxonKey is Helianthemum viscidulum Boiss.", "TaxonKey is Lecanora lamarckii (DC.) Rabenh.", "TaxonKey is Anthyllis plumosa Cullen ex E.Domínguez", "TaxonKey is Cytisus malacitanus subsp. moleroi (Fern.Casas) Á.Lora, Hern.Berm. & Prados", "TaxonKey is Sarcocapnos crassifolia (Desf.) DC.", "TaxonKey is Luzula hispanica Chrtek & Krísa", "TaxonKey is Aquilegia cazorlensis Heywood", "TaxonKey is Amelanchier rotundifolia (Michx.) M.Roem.", "TaxonKey is Sorbus aria subsp. aria", "TaxonKey is Salix eleagnos subsp. angustifolia (Cariot) Rech.fil.", "TaxonKey is Acinos alpinus (L.) Moench", "TaxonKey is Helichrysum italicum (Roth) G.Don", "TaxonKey is Silene auriculifolia Pomel", "TaxonKey is Helichrysum stoechas (L.) Moench", "TaxonKey is Equisetum arvense", "TaxonKey is Foeniculum vulgare Mill.", "TaxonKey is Lavandula dentata L.", "TaxonKey is Lavandula latifolia Medik.", "TaxonKey is Lavandula stoechas L.", "TaxonKey is Marrubium supinum (Stephan ex Willd.) Hu ex P'ei", "TaxonKey is Origanum virens Hoffmanns. & Link", "TaxonKey is Plantago major L.", "TaxonKey is Rosmarinus officinalis L.", "TaxonKey is Cytisus moleroi Fern.Casas", "TaxonKey is Salvia lavandulifolia Vahl", "TaxonKey is Satureja obovata (Ruiz & Pav.) Briq.", "TaxonKey is Sideritis hirsuta Sieber ex Benth., 1834", "TaxonKey is Sideritis leucantha Cav.", "TaxonKey is Smilax aspera L.", "TaxonKey is Scleranthus burnatii Briq.", "TaxonKey is Teucrium capitatum L.", "TaxonKey is Teucrium fruticans L.", "TaxonKey is Scabiosa saxatilis var. grosii (Font Quer) Fern.Casas" ] } ] } The dataset includes 174734 records from 98 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002523-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences